Hubungan Tingkat Pengetahuan Tentang Ulkus Diabetik Dengan Perawatan Kaki Diabetik Pada Pasien Diabetus Melitus Di Persadia Cabang Kota Surakarta - Rahmawati, Umi Nur, Fahrun Nur R, S.Kep.,Ns.,M.Kep (2017)
One of the complications of diabetes mellitus is a problem in the feet commonly called diabetic foot. Action should be taken in foot care is to detect abnormalities early foot. DM patients' knowledge about the disease and its complications can be influential in the effort to prevent diabetic foot. if the patient has adequate knowledge so they can make the prevention of diabetic ulcer. This study aims to determine the relationship of the level of knowledge about the treatment of diabetic ulcers of diabetic foot patients Persadia diabetus mellitus in Surakarta city branch. This research is a quantitative research with descriptive analytic method with cross sectional approach. Samples are 44 people who obtained using purposive sampling method. Collecting data using a questionnaire, while analysis using Spearman Rank. Conclusions showed the level of patients' knowledge about the ulcers of diabetic largely enough, the level of treatment of diabetic foot in patients with diabetes mellitus mostly pretty, and there is a relationship between the level of knowledge about the ulcers of diabetic with foot care to patients with diabetes mellitus in Persadia Branch of Surakarta, namely the better knowledge the better the treatment